Sumbangan Pendidikan Islam dalam Mengantar Pluralisme dan Multikulturalisme Indonesia - Humaisi, M. Syafiq (FKIP Universitas Wisnuwardhana, 2020)
The legality of Islamic education only received recognition after the issuance of Law Number12 of 2012, concerning higher education. The law stipulates that Islamic education is included in the clusters of religious knowledge. In the explanation of Article 10 paragraph 2 of the Law, it explains that; The religious knowledge cluster is a scientific cluster that studies beliefs about divinity or monotheism as well as sacred religious texts, including the science of ushuluddin, the science of syari'ah, courtesy science, dakwah science, education science, Islamic philosophy and thought, Islamic economics, Hindu religious education, Hindu religious philosophy, Buddhist religious education, Buddhist information science, Buddhist philosophy, Christian religious education, Catholic religious education, missiological theology, pastoral counseling, and religious education of Confucianism. However, academically the existence of Islamic education has been started since the sending of the messenger of Allah Muhammad Saw, in Mecca and continued to Medina after the Migrate incident.